Determining mass limits around HD 163296 through SPHERE direct imaging data. Issue 1 (18th June 2019) - Mesa, D; Langlois, M; Garufi, A; Gratton, R; Desidera, S; D'Orazi, V; Flasseur, O; Barbieri, M; Benisty, M; Henning, T; Ligi, R; Sissa, E; et al.
ABSTRACT: HD 163296 is a Herbig Ae/Be star known to host a protoplanetary disc with a ringed structure. To explain the disc features, previous works proposed the presence of planets embedded into the disc. We have observed HD 163296 with the near-infrared (NIR) branch of SPHERE composed by IRDIS (InfraRed Dual-band Imager and Spectrograph) and IFS (integral field spectrograph) with the aim to put tight constraints on the presence of substellar companions around this star. Despite the low rotation of the field of view during our observation we were able to put upper mass limits of few MJup around this object. These limits do not allow to give any definitive conclusion about the planets proposed through the disc characteristics. On the other hand, our results seem to exclude the presence of the only candidate proposed until now using direct imaging in the NIR even if some caution has to be taken considered the different wavelength bands of the two observations.